Epidermal growth factor receptor juxtamembrane region regulates allosteric tyrosine kinase activation - Thiel, Kristina W. (National Academy of Sciences, 2007)
Structural studies of the extracellular and tyrosine kinase domains of the epidermal growth factor receptor (ErbB-1) provide considerable insight into facets of the receptor activation mechanism, but the contributions of other regions of ErbB-1 have not been ascertained. This study demonstrates that the intracellular juxtamembrane (JM) region plays a vital role in the kinase activation mechanism. In the experiments described herein, the entire ErbB-1 intracellular domain (ICD) has been expressed in mammalian cells to explore the significance of the JM region in kinase activity. Deletion of the JM region (ΔJM) results in a severe loss of ICD tyrosine phosphorylation, indicating that this region is required for maximal activity of the tyrosine kinase domain. Coexpression of ΔJM and dimerization-deficient kinase domain ICD mutants revealed that the JM region is indispensable for allosteric kinase activation and productive monomer interactions within a dimer. Studies with the intact receptor confirmed the role of the JM region in kinase activation. Within the JM region, Thr-654 is a known protein kinase C (PKC) phosphorylation site that modulates kinase activity in the context of the intact ErbB-1 receptor; yet, the mechanism is not known. Whereas a T654A mutation promotes increased ICD tyrosine phosphorylation, the phosphomimetic T654D mutant generates a 50% reduction in ICD tyrosine phosphorylation. Similar to the ΔJM mutants, the T654D mutant ICD failed to interact with a wild-type monomer. This study reveals an integral role for the intracellular JM region of ErbB-1 in allosteric kinase activation.